Treating a patient with pan-resistant Acinetobacter: a case study - Nazar, Maimoona; Nasir Ashraf; Laiba Sultan; Laiba Sultan (Journal of the Pakistan Medical Association, 2024)
Acinetobacter has emerged as a highly important organism in global healthcare, owing to its propensity to develop pan-resistance. This resistant pathogen poses a significant challenge to healthcare professionals because it not only restricts patient care through ineffective treatment modalities but also leads to high mortality and morbidity rates. The case of a 22-year-old young man reporting to the Emergency department (ER) of Pakistan Institute of Medical Sciences (PIMS), Islamabad, on 6th June, 2023 is presented. He complained of fever accompanied with seizures which gave a suspicion of autoimmune encephalitis or viral haemorrhagic fever. Despite initial therapeutic interventions, the patient’s condition worsened, prompting further investigations. Culture and sensitivity testing of tracheal secretions revealed pan-resistance, and subsequent treatment with a combination of antibiotics including Tigecycline and Colistin, yielded a favourable response. —Continue